Impacto de la intervención farmacéutica en la adherencia al tratamiento antirretroviral en pacientes de un hospital de Lima (Perú). - Tafur Valderrama, E.J. (2014)
Introduction: Pharmaceutical care improves medication adherence that is why is important that the pharmacist uses instruments to evaluate and improves it through pharmaceutical intervention at pharmaceutical care. Objective: To evaluate the impact of the pharmaceutical intervention in the improvement of the medication adherence of the patients with HIV and AIDS, and to identify the factors that infl uence on medication adherence and which one could be modifi ed by the pharmaceutical intervention during pharmaceutical care. Methods: Pharmacotherapeutic follow-up was realized for 23 months to 52 patients, older than 18 years, with antiretroviral treatment for up to three months, consent informed was obtained from patients. Medication adherence was evaluated with CEAT-HIV (questionnaire to evaluate the adhesion to the antiretroviral treatment) at the beginning and at the end of the study (6 months). Results: The fi nal score from CEAT-HIV (p <0.05; 95% IC), treatment compliance (p <0.001) and patient’s beliefs to the disease and antiretroviral treatment (p <0.001) improved signifi cantly with the pharmaceutical intervention. The more frequent pharmaceutical intervention was education to the patient to increment the adherence to the treatment (46%). Conclusion: These results demonstrate that the pharmacists’ intervention through pharmacotherapeutic follow-up improves the adherence to the antiretroviral treatment. The pharmacist was able to improve aspects of compliance and patient’s beliefs about the treatment and disease. The pharmacist could utilize CEAT-VIH as an instrument to evaluate the adherence in HIV/AIDS patients.